PENGARUH PENGAWASAN, DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KESELAMATAN DAN KESEHATAN KERJA KARYAWAN PADA PT. BUMI MULIA PERKASA DUMAI - Wiraandika, Gatra (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to determine and analyze the influence of supervision,discipline and physical work environment affect the safety and health of employees atPT. Bumi Mulia Perkasa Dumai. Population in this research is 326 employees at PT.Bumi Mulia Perkasa Dumai. While the number of samples at PT. Bumi Mulia PerkasaDumai is 77 people. The instrument used for data collection is by the Ordinal scalemodel questionnaire. To test the hypothesis used descriptive analysis and multiplelinear regression analysis.The results of data analysis show that the Supervision has asignificant and positive influence on Occupational Safety and Health, Displin has asignificant and positive influence on Occupational Health and Safety, Physical WorkEnvironment has a significant and positive influence on Occupational Health and Safetyand Supervision, Work Discipline and the Physical Work Environment together have asignificant and positive influence on Occupational Safety and Health.It is recommended this research to the leaders and agencies in making policiesconcerning supervision, discipline, physical work environment and occupational safetyand health as well as additional reference materials for other researchers who want toanalyze the same problem.